1997
DOI: 10.1007/s002590050196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dobutamine stress echocardiography and technetium-99m sestamibi single-photon emission tomography for the diagnosis of coronary artery disease in hypertensive patients with and without left ventricular hypertrophy

Abstract: Stress echocardiography has been considered an accurate method for the diagnosis of coronary artery disease in hypertensive patients and in patients with left ventricular hypertrophy. In contrast, the specificity of myocardial perfusion scintigraphy in these patients has been questioned. The aim of this study was to compare the accuracy of these two imaging modalities in conjunction with dobutamine stress test for the diagnosis of coronary artery disease in hypertensive patients with and without left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Concordant with previous reports, we demonstrated that in patients with normal LV mass and normal geometry, DSMR-wall motion has both high sensitivity and high specificity for the detection of hemodynamically relevant CAD. 1,5,6 We could show that an absolute increase in LV mass or septal wall thickness did not adversely affect accuracy of DSMR-wall motion, which is in line with prior studies using echocardiography 18 and cardiovascular MRI (CMR). 9 Although CMR is regarded for its superior image quality that allows for a consistently high definition of the endocardial border in all LV segments, our study demonstrates that LV geometry may limit the diagnostic capability of wallmotion analysis for the detection of stress-inducible ischemic reactions.…”
Section: Discussionsupporting
confidence: 72%
“…Concordant with previous reports, we demonstrated that in patients with normal LV mass and normal geometry, DSMR-wall motion has both high sensitivity and high specificity for the detection of hemodynamically relevant CAD. 1,5,6 We could show that an absolute increase in LV mass or septal wall thickness did not adversely affect accuracy of DSMR-wall motion, which is in line with prior studies using echocardiography 18 and cardiovascular MRI (CMR). 9 Although CMR is regarded for its superior image quality that allows for a consistently high definition of the endocardial border in all LV segments, our study demonstrates that LV geometry may limit the diagnostic capability of wallmotion analysis for the detection of stress-inducible ischemic reactions.…”
Section: Discussionsupporting
confidence: 72%
“…Summarised data from two studies ( Table 2, 286 patients) have demonstrated a somewhat higher sensitivity for perfusion imaging compared to stress echocardiography (87 vs 74%, P<0.005), and confirmed the lower specificity for perfusion imaging (44 vs 85%, P<0.001). 36,37 The diagnosis of coronary artery disease in women may be more challenging due to the lower prevalence of coronary artery disease. In addition, single-vessel disease is a common finding in women.…”
Section: Detection Of Coronary Artery Diseasementioning
confidence: 99%
“…Of those who had an exercise stress and an interpretable ECG, the sensitivity and specificity of the exercise ECG was only 51% and 43% respectively. 17 Elhendy and colleagues, 18 in a population of 84 hypertensive patients, 70% with and 30% without LVH, compared sesta-MIBI SPECT and stress echocardiography for the detection of CAD. Overall 79% of patients had significant CAD.…”
Section: Myocardial Perfusion Imaging In the Presence Of Lvhmentioning
confidence: 99%
“…The sensitivities and specificities for MPI and DSE were 98% and 88% and 36% and 84% respectively. 23 Elhendy and co-workers 18 found that the overall sensitivity, specificity and for the detection of significant CAD using DSE to be 73% and 83%. There was no significant difference in sensitivity and specificity in the presence of LVH.…”
mentioning
confidence: 99%
See 1 more Smart Citation